Driving Performance Through Motivation: How Productive Behavior Mediates Employee Performance in a Government Revenue Institution: English - Lalu Rahmat Iqbal; Abdul Azis Bagis (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The present research investigation examines the effect of work motivation on employee performance, both in a direct manner and through an indirect mechanism through productive behavior functioning as a mediator. A quantitative explanatory research design utilizing survey-based data was implemented from 91 employees of a government institution in Nusa Tenggara Barat, Indonesia. Data were gathered using structured questionnaires and subsequently analyzed employing IBM SPSS Statistics 23, employing validity and reliability assessments, classical regression assumption examinations, multiple linear regression, determination coefficient analysis, F-statistics, t-statistics, and the Sobel test. The findings demonstrate that work motivation exerts a significant effect on productive behavior and employee performance, and that productive behavior, in turn, shows a positive and statistically significant impact on employee performance. The Sobel test confirms that productive behavior partially acted as an intermediary in the relationship linking work motivation and employee performance. These results emphasize the importance of enhancing employee motivation and productivity in enhancing performance outcomes, offering practical contributions to human resource management within public-domain organizations.